Urgensi Sinergi PPATK dan Aparat Penegak Hukum dalam Penyitaan Aset Kripto Sebagai Hasil Tindak Pidana Pencucian Uang: Telaah Kritis atas Pedoman Jaksa Agung Nomor 7 Tahun 2023 - Beren Ginting; Dwi Novantoro; Halif (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the normative framework for the confiscation of crypto assets resulting from money laundering and examine the role of the Financial Transaction Reports and Analysis Center (PPATK) and the position of Attorney General's Guideline Number 7 of 2023 within the Indonesian legal system. The study employed normative legal methods with a statutory and conceptual approach. The results indicate that the PPATK plays a central role as a Financial Intelligence Unit through the analysis of suspicious financial transactions, asset tracking, temporary suspension of transactions, and provision of financial intelligence to law enforcement officials. Attorney General's Guideline Number 7 of 2023 does not conflict with higher-level regulations because it only regulates the technical aspects of handling crypto assets. However, as an internal policy, the guideline has limited binding power, requiring more comprehensive regulations to strengthen crossagency coordination and the effectiveness of asset recovery.